PENGEMBANGAN MAKANAN FORMULA ANAK BALITA MENGGUNAKAN BERBAGAI JENIS IKAN LAUT DAN RUMPUT LAUT - Uken Soetrisno; Elisa D. Julianti (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2007)
ABSTRACT Background:  Deficiency in energy, protein and micronutrient of children under five years can cause growth faltering, besides the delayed in mental development and easily infected. Indonesia is highly potential in marine food sources, included fishes and seaweeds which are rich in macro and micronutrients. Formulated food made of fish were well accepted, but was not proven to improve growth significantly; while usage of seaweeds has not been explored. Objectives:  To produce formulated food, which contain macro and micronutrient that important for growth and mental development. The results will encourage usage of marine food sources and development of feasible food processing. Methods:  Food base included carbohydrate sources: rice flour, sweet corn, yellow yam, and sweet plaintain; protein sources: stingray, shark, tuna, greyfish and soybean. Sources of micronutrients were vegetables and seaweeds. Cooking oil and sugar were added to make 400 kCal energy content per 100 g formula and improve taste. Quality evaluation were tested: protein score, nutrient content, sensoric test and water absorbability of the formulated food.Results: Four kinds of formula were developed and well accepted by the panelist. Those formula have low water absorbtion and good sensoric quality. Protein scores are 84-97%, higher than that of soybean. Content of folate, vitamin A, iodine and Zn per 100 g formula can fulfill 70-110% daily allowance of children under five years old. Conclusions: Formulated food based on marine fishes and seaweeds were well accepted, with calculated protein scores were higher than soybean’s. Micronutrients content were high in all formula. There is a need to explore all potential benefits of the marine food sources, both protein sources and seaweeds, to develop other formulated foods for children. [Penel Gizi Makan 2007, 30(1): 1-7] Keywords:  food formula, marine fishes, seaweeds, sensoric quality, children under five years old.